Cost-effectiveness of a bacterial-binding dressing to prevent surgical site infection following caesarean section. (2nd April 2019) - Stanirowski, Paweł Jan; Davies, Heather; McMaster, Jessica; Mealing, Stuart; Sawicki, Włodzimierz; Cendrowski, Krzysztof; Posnett, John
Abstract : Objective: A randomised controlled trial (RCT) recruited women undergoing caesarean section (CS) in Poland. The aim of the trial was to assess the efficacy of a dialkylcarbamoyl chloride (DACC)-impregnated surgical dressing (bacterial-binding dressings) compared with standard of care (SoC) in preventing surgical site infection (SSI). The aim of the present analysis was to evaluate the cost-effectiveness of the bacterial-binding dressings in the context of the UK National Health Service (NHS). Method: The clinical trial randomised patients to a bacterial-binding dressing (n=272) or a standard surgical dressing (n=271). The study recorded the presence of SSI and associated resource use up to 14 days postoperatively. To generalise results to the NHS, UK unit costs were applied to resource use recorded in the trial. An alternative approach applied a single UK-specific episode cost per SSI. Results: There were 543 women recruited to the trial. SSI rates were 5/272 (1.8%) and 14/271 (5.2%) for bacterial-binding dressings and SoC, respectively (p=0.04). Patients in the bacterial-binding dressing group had six fewer outpatient visits and 33 fewer hospital bed-days. The mean length of SSI-attributable hospitalisation was 2.36 days. Applying UK unit costs at 2017 prices to resource use recorded in the trial, costs of SSI prophylaxis and treatment were £48.97 and £24.69 per patient in the SoC and bacterial-binding dressing groups respectively, a difference of £24.27 (49.6%) per patient. The alternative costing approach produced a cost saving of £119 (57.6%) per patient with the bacterial-binding dressing. Conclusion: Use of bacterial-binding dressings following CS has the potential to reduce the incidence of SSI and costs to the NHS.